Fire focus and its relationships with rainfall and air temperature in Jataí, Goiás, Brazil - Corrêa, Thomas Rieth; Dias, Daniela Pereira (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2023)
Monthly and annual changes in rainfall and air temperature may favor the occurrence of forest fires, which can be associated with fire focus observed via satellite. The objective of this study was to evaluate the annual variability of rainfall and air temperature and relate them to the fire focus observed in Jataí, Goiás, Brazil, between 2008 and 2021. Microclimatic data (rainfall, and minimum, mean and maximum temperature) and the number of daily fire focus from 2008 and 2021. According to the climatological normal (1981-2010) of Jataí, the mean values of rainfall (Pmm) and air temperature (Tar) were, respectively, 1,648.9 mm and 22.4 oC. In the period studied, Pmm ranged from 1,108.4 mm (2019) to 1,868.0 (2008), ant Tar presented in 2021, 22.1 oC, and in 2014, 23.72 oC. The driest months were from May to October, especially July and August, however the hottest were September and October. Between 2008 and 2021, were observed 1,270.0 fire focus, with greater concentration in the driest months. Although there was a correlation between the microclimatic variables and fire focus, they were not significant (p > 0.05). This allows us to infer that the low annual variability of Pmm and Tar (minimum, mean, and maximum) meant that there was no significant correlation with the number of hot spots observed in Jataí between 2008 and 2021.